Implementation of Outdoor Learning to Improve IPAS Interest and Outcomes at Elementary School - Ginong Pratidinanto; Ibadullah Malawi; Sudarmiani Sudarmiani (EDUJAVARE: International Journal of Educational Research, 2026)
This research was driven by the low learning interest and achievement in Science and Social Studies (IPAS) among third-grade students at SDN Pare 4, resulting from teacher-centered instruction and limited meaningful learning experiences. The study aimed to describe the implementation of the outdoor learning method and evaluate its effectiveness in improving students' learning interest and IPAS achievement. A mixed-methods approach was employed using Classroom Action Research conducted in two cycles consisting of planning, action, observation, and reflection. Data were collected through observations, achievement tests, learning interest questionnaires, interviews, and documentation, and analyzed using descriptive qualitative and quantitative techniques. The results showed that outdoor learning significantly improved both the learning process and student engagement. Students' average learning interest increased from 55.2% in the pre-cycle to 94.5% in Cycle II, while average learning achievement improved from 68.75 to 91.25, with classical mastery reaching 100%. The study concludes that outdoor learning is an effective instructional strategy for enhancing learning interest and IPAS achievement and provides a contextual and engaging learning environment for primary school students.